More than a biomarker: the systemic consequences of heparan sulfate fragments released during endothelial surface layer degradation (2017 Grover Conference Series) - Oshima, Kaori (Pulm Circ, 2017)
Advances in tissue fixation and imaging techniques have yielded increasing appreciation for the glycosaminoglycan-rich endothelial glycocalyx and its in vivo manifestation, the endothelial surface layer (ESL). Pathological loss of the ESL during critical illness promotes local endothelial dysfunction and, consequently, organ injury. Glycosaminoglycan fragments, such as heparan sulfate, are released into the plasma of animals and humans after ESL degradation and have thus served as a biomarker of endothelial injury. The development of state-of-the-art glycomic techniques, however, has revealed that these circulating heparan sulfate fragments are capable of influencing growth factor and other signaling pathways distant to the site of ESL injury. This review summarizes the current state of knowledge concerning the local (i.e. endothelial injury) and systemic (i.e. para- or endocrine) consequences of ESL degradation and identifies opportunities for future, novel investigations.